"He Has Rescued Me from Danger" - Sarah Bishop (Voices, 2024)
The Ethio-South Sudanese border is characterized by instability and conflict. Most populations in this area have experienced violence and displacement and face ongoing insecurity and political inequality. During my fieldwork in the region, several composers gave accounts of how composing and singing Christian songs provided them with comfort and hope in times of hardship, particularly following episodes of violence. Using ethnographic research and interviews as primary methodologies, this article explores how these individuals use religious music-making as a means of coping and resilience in the wake of trauma. The primary goal of this article is to provide a platform for their stories. The secondary goal is to explore resonances between their accounts and scholarly observations about potential roles of music-making in trauma resilience across disciplines. I focus particularly on themes of embodied music-making, community connection, and spirituality. All point to the same phenomenon: that music can play a role in human resilience and meaning-making. Finally, I make suggestions on how to enhance mental health care in culturally-relevant ways in a religious society such as in Ethiopia, as well as draw out cross-cultural implications for mental health care in the western system.